Carriage of the zoonotic organism Streptococcus suis in chicken flocks in Vietnam - Nhung, NT; Yen, NTP; Cuong, N; Kiet, BT; Hien, VB; Campbell, J; Thwaites, G; Baker, S; Geskus, R; Ashton, P; Carrique-Mas, J (Wiley, 2020)
Streptococcus suis infections are an emerging zoonotic agent causing severe disease in humans and a major pig pathogen worldwide. We investigated the colonization of S. suis in healthy chickens in different flocks (n = 59) as well as in‐contact pigs in farms with S. suis‐positive chickens (n = 44) in the Mekong Delta of Vietnam. Streptococcus suis was isolated from 20 (33.9%) chicken flocks and from all pigs investigated. Chicken isolates formed a distinct genotypic cluster compared with pig and human strains, although two chicken isolates (10%) clustered with pig isolates. Chicken isolates had unusually high levels of resistance against tetracycline (100%), clindamycin (100%) and erythromycin (95%); and intermediate resistance against penicillin (35%) and ceftriaxone (15%). Our findings suggest that chickens may potentially represent a source of S. suis infection to in‐contact humans and pigs.